Interfaces entre a política habitacional e o Plano Diretor Participativo na metrópole Fortaleza-CE / Relations between the housing policy and participatory master plan in metropolis Fortaleza, Ceará, Brazil - Elizete de Oliveira Santos (Sociedade & Natureza)
The housing question appears as essential element to understanding the production, consumption and appropriation processes of urban space, illuminating the relationship between sociospatial segregation and real state speculation that govern the brazilians' cities structuring. This paper proposes to discuss the relations between the Participatory Master Plan of Fortaleza (PDPFor) and the Municipal Housing Policy (PHIS), aiming to contribute to the reflection of the importance of the urban and housing policies integration. The text is divided into three parts: the first discusses the context of the emergence of the master plans "new generation" in Brazil; the second reconstructs the preparation process of the PDPFor and PHIS; and the third proposes a questioning about the dialogue between the urban and housing political, based on the analysis of the content of PHIS and housing policy chapter in PDPFor.